PELAKSANAAN TUGAS POLRI MENDUKUNG PROTOKOL KESEHATAN SELAMA PANDEMI COVID-19 DALAM RANGKA TERWUJUDNYA SITUASI KAMTIBMAS YANG KONDUSIF - Phami Tomas; Abdul Wahid; Rohadi Rohadi (Jurnal De Jure Muhammadiyah Cirebon, 2021)
During this pandemic, the role of the National Police in the framework of security, creating a very large conducive situation, as a front line in creating a situation of the security and public order (Kamtibmas), especially when assisting local governments in the application of some policies during the Covid-19 pandemic, such as the implementation of Large-Scale Social Restrictions (PSBB), security of health protocols, preventive measures of swarming communities and preventing crime has become an inherent part of human life history since ancient times until now. Crime has a damaging effect on the social order, creates insecurity and fear, and adds a huge economic burden to society. The research problems are the police's steps in implementing Kamtibmas during the Covid-19 pandemic and the Police's steps in supporting the compliance of health protocols in the community during the Covid-19 pandemic to realize a conducive kamtibmas situation. This research uses a non-doctrinal method with the normative juridical approach, using a conceptual approach. Keywords: Implementation of Duties, Police, Health Protocols, Pandemic Covid-19.